Tinjauan Kewenangan Ombudsman Republik Indonesia Dalam Penyelesaian Laporan Masyarakat - Firmansyah, Didi; Nugroho, Sigit (PROGRESIF: Jurnal Hukum, 2023)
In carrying out the task of completing community reports, the Ombudsman of the Republic of Indonesia is not only known for providing recommendations but also the Ombudsman of the Republic of Indonesia has the final product of completing the report, namely the Final Report of the Examination Results. Therefore, this study aims to: explain the legal review of the Final Report of the Examination Results as part of the series of examinations of community reports that have a relationship with providing recommendations if corrective actions in the Final Report of the Examination Results are not implemented by the Public Service Provider in the findings of mal-administration. The method used in this study is the normative juridical method. The results showed that the Final Report of the Examination Results is a whole series of processes for receiving and verifying reports with formal and material requirements which will then be followed up in the examination process, the product of the Ombudsman's supervision service is the Final Report of the Examination Results. So the Ombudsman of the Republic of Indonesia does not just provide recommendations, because of the position of the Ombudsman of the Republic of Indonesia as a state institution that exerts influence in a persuasive approach in handling community reports related to mal-administration. One of the main concerns of this study is that the Final Report on the Results of the Examination has not been included in the Ombudsman Law of the Republic of Indonesia so that hierarchically the power of the Ombudsman of the Republic of Indonesia is in the recommendations. However, the existence of the Final Report of the Examination Results as an effort by the Ombudsman of the Republic of Indonesia to encourage the improvement and improvement of public services at the encouragement of independent public service providers